Innovative Smart Water Management System Using Artificial Intelligence - et.al, Aamir Khambati (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research paper proposes an effective solution to the critical problem of management of water resources. With the growing awareness of the need for water conservation, the world is gearing to accommodate and implement latest technology for the optimum utilisation of the drying up reservoirs. This paper aims at developing a cost effective, portable and ready to plug mechanism labelled as “Innovative Smart Water Management System Using Artificial Intelligence” which shall monitor the proportion of water usage per household and keep a tracking on metric usage on the water usage on a weekly, monthly or a yearly basis. The data generated will be established and collected in the Firebase server. Based on the collected data, it shall also make predictions on the usage and hence allocate resources in a controlled fashion as per requirement. Later the data will be modelled in Time Series fashion to generate real time prediction of water consumption for the household respectively. The water consumer can track the usage by a custom-made android application on MIT App Inventor. Extensive, detailed instructions have been provided on the initial setup procedure and installation. The water monitoring module is used on a daily basis and a tab is kept on the amount of water spilled. This will keep a check on the casual approach of people towards water. It will also encourage a more systematic method to handle water resources and hence would result in better conservation efforts